Os afetos tristes e sua contenção na ética de Spinoza - Alves, Damiana Bezerra (2021)
The present thesis has as object of research the sad affectus and their containment in the Ethics of Spinoza. In its unraveling, these affectus will be treated and understood as something typical to the human condition, having a fundamental participation in the nature of the individual, and may be subject to containment or not. And this is what will if verify in this work. Therefore, we assume as central problem the question of knowing If there is in Spinoza's Ethics a theorization on the containment of the so-called ―sad affectus‖. We know, from the point of view of practical philosophy, the difficulties that human beings have in "refraining", "dominating" or even " educating" their feelings. In this way, it is hypothesized that such a containment of the sad affectus is viable to be found in Spinoza's Ethics in a partial way, notably in parts IV and V, to the extent that these affectus, for Spinoza, constitute central factors, allowing us to perceive that one of the remedies for the solution of the problem in investigation is in the intellectual strength of the subject, that is, in the comprehension (even if this is it limited and incomplete) because through hers we can go deeper into each affectus that directs us and try to understand them and, above all, know them so that we can know the best way to "contain them‖, when necessary, and centrally if it is possible for us. The method that will be used is an integrative and narrative literature review, starting from the philosopher's own works as well as his respective commentators, national and foreign. This thesis is structured in three chapters in which they will be developed as follows: in the first chapter the study will be surrounded by the work and the historicalphilosophical context in which the philosophical system of Spinoza emerged, in special its 'Ethics'. In the second, we will go into the matter of sad affectus in order to unveil this category and, within this ambit, We will dwell in detail on these affectus, on their primary division and also on the two other originating affectus, namely: of desire and joy and, lastly, In the third chapter, we will deal with the knowledge of the affectus and their possible containment, to verify the proof or not of the hypothesis related to the problem proposed by the analysis of the object.